Quality of Life Improvement Through Social Cohesion - Ostasiewicz, Walenty (Poprawa jakości życia poprzez spójność społeczną, 2009)
The aim of this paper is to present briefly, rather than discuss systematically, the personal view on the problem of quality of living studies. In the most concise form the position advocated in this paper is expressed by the following slogans. Values, rather than prices. Human being has dignity not a price. Contractorian ethics instead of utilitarian one. The three: state, society and market, are rather the trees planted by welfare society than a member of a ménage à trois. Solidarity is more natural for humankind than exchange. Rather functioning, i.e., improvement by empowerment than opulence should be a criterion for human activity. Deliberation on quality of life should be more philosophically founded. To establish shared and agreed values is much more important problem to study than the study of the women’s satisfaction from markets visiting or the usefulness of telephones
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 41-49